Pelatihan Model Pembelajaran Terbaru Teaching Games For Understanding (TGFU) Pada Guru Penjasorkes - PTri Setyo Guntoro; Sutoro Sutoro; Rodhi Rusdianto Hidayat (Jurnal Berkarya Pengabdian Masyarakat, 2022)
Purpose of this training is to improve the pedagogic competence of physical education teachers in Jayapura city. We do through training in the Teaching Games For Understanding (TGFU) learning model. The training approach uses discourse and practicum methods (class and field). There was an increase in the knowledge and teaching skills of physical education teachers throughout the Jayapura city using the TGFU learning model. There is a significant difference between the average knowledge of participants before and after being given the training where the value of Sig. (2-tailed) < 0.05 (p value = 0.000). This value indicates that the training provided significantly affects the participants' knowledge of the Teaching Games for Understanding learning model. Through the TGFU learning model, it can increase student interest and increase the achievement of physical education learning objectives. Through the TGFU learning model, students' interest in physical education has increased again even though they have been undergoing online learning for a long time.